China's geography : globalization and the dynamics of political, economic, and social change /: globalization and the dynamics of political, economic, and social change. (2021) - Veeck, Gregory, 1956-; Pannell, Clifton W; Shen, Xiaoping; Huang, Youqin
No abstract available